Large and Increasing Biospheric Productivity of Northern Ecosystems - Cuntz, Matthias; Smith, Benjamin; Canadell, Josep G.; Knauer, Jürgen; Haverd, Vanessa (Geophysical Research Letters, 2025)
Plants take up carbon dioxide (CO2) through photosynthesis. How this will change with rising CO2 concentrations in the atmosphere will strongly determine future climate change. An increase in the seasonal variations of atmospheric CO2 in recent decades indicates a positive trend in photosynthetic carbon uptake. We combined data-driven seasonal cycles of plant productivity with carbon sinks across the range predicted by current biospheric process models to explain the seasonal variations of CO2 at high and low northern latitudes over the past 40 years. We find that increases in seasonal variations can only be explained by a larger gross primary productivity (GPP) of northern ecosystems than most current estimates and by an increase of GPP about proportional to the increase in atmospheric CO2, also larger than most current estimates. Our results provide an improved constraint to estimate the future behavior of the terrestrial carbon sink.
Publisher Copyright: © 2025. The Author(s).
Keywords: atmospheric CO2; CO2 fertilization; gross primary productivity; northern hemisphere; seasonal cycle